2020
DOI: 10.1590/s1984-29612020057
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evaluation of piroplasms and hematological changes in canine blood stored in a clinical laboratory in Niterói, Rio de Janeiro

Abstract: Piroplasm species were analyzed by molecular tools in total 31 blood samples from positive dogs, previously checked by stained slides, stored until DNA extraction between 2016 to 2018 in the laboratory Clinical Analyzes in Niterói, Rio de Janeiro. The piroplasms were identified by PCR, targeting the 18S rRNA gene and sequencing. From the total number of samples only 24 (77.4%) were positive and show adequate nucleotide sequences for interpretation with identity between 93%-100% with Babesia vogeli in compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 36 publications
0
4
0
10
Order By: Relevance
“…The molecular analyses of the present study only identified B. vogeli. In fact, B. vogeli is the piroplasmid species that has been most detected in dogs in different regions of Brazil [16,18,25,28,[30][31][32][35][36][37], and in other countries [37][38][39][40][41][42]. However, in addition to this species, the piroplasmid R. vitalii has also been detected in dogs in the southern region of Brazil and in municipalities in the mountain region of the state of Rio de Janeiro, by means of molecular tools [13,14,16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The molecular analyses of the present study only identified B. vogeli. In fact, B. vogeli is the piroplasmid species that has been most detected in dogs in different regions of Brazil [16,18,25,28,[30][31][32][35][36][37], and in other countries [37][38][39][40][41][42]. However, in addition to this species, the piroplasmid R. vitalii has also been detected in dogs in the southern region of Brazil and in municipalities in the mountain region of the state of Rio de Janeiro, by means of molecular tools [13,14,16].…”
Section: Discussionmentioning
confidence: 99%
“…Although no census data on the canine population are available, it can be stated that in a general manner, the pet population has been increasing proportionally with increases in the human population. This has consequently favored increasing populations of ixodids and of the infectious agents that these vectors transmit, such as piroplasmids [18]. In general, the intensity of dog infestations by R. sanguineus, its main host, can vary, both geographically and seasonally, being higher in stray dogs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As manifestações clínicas nas hemoparasitoses são, geralmente, semelhantes e inespecíficas. Os principais sinais associados à enfermidade e relatados pela literatura são: apatia, anorexia e febre; acompanhados de algumas alterações hematológicas, como anemia e trombocitopenia (Prado et al, 2019& Santos et al, 2020. As alterações clínicas e patológicas que ocorrem em cães infectados podem variar conforme a espécie de Babesia envolvida na infecção (Santos et al, 2020).…”
Section: Introductionunclassified
“…Within this context, helminths and apicomplexan protozoa are included, which can infect domestic animals in urban and rural environments. [ 6 7 8 9 ]…”
mentioning
confidence: 99%